Effect of sublethal concentrations of the antiparasitic ivermectin on the polychaeta species Hediste diversicolor: biochemical and behavioral responses - Nunes, Bruno (2022)
Pharmaceutical drugs have emerged as major micropollutants in aquatic ecosystems. Their presence has been systematically reported in monitoring surveys, and their wide distribution and constant presence in the wild is a direct consequence of their massive use, in both human and veterinary therapeutics. Drugs used to treat parasitic infections in livestock are major contaminants, given the amounts in which they are administered, and reach the aquatic compartment in high amounts, where they may affect non target species. Some of these drugs are prone to find their final deposit in sediments of estuarine areas, exerting their toxic effects preferentially at these locations. Sediment dwelling organisms of coastal areas, such as polychaetas, are especially prone to have their major physiological functions compromised after being exposed to pharmaceutical drugs. Ivermectin is one of the most used antiparasitic drugs, and its effects are not limited to biochemical traits, but also behavioral features may be compromised considering their neurotoxic actions. Despite these putative effects, little is known about their toxicity on polychaetas. The present study aimed to characterize the toxicity of realistic levels of ivermectin on the polychaeta Hediste diversicolor, in biochemical and behavioral terms. The obtained results showed that low levels of ivermectin are capable of causing significant disturbances in mobility and burrowing activity of exposed worms, as well as alterations of metabolic and anti-oxidant defense efficacy of exposed animals, suggesting that its environmental presence may mean a major environmental concern.